LAVENDER AROMATERAPHY AS A RELAXANT - IGA Prima Dewi AP (Universitas Udayana, 2013)
Aromatherapy is a kind of treatment that used aroma with aromatherapy essential oil. Extraction process from essential oil generally doing in three methods, there are distilling with water (boiled), distilling with water and steam, and distilling with steam. One of the most favorite aroma is lavender. The main content from lavender is linalyl acetate and linalool (C10H18O). Linalool is main active contents in lavender which can use for anti-anxiety (relaxation). Based on some research, the conclusion indicates that essential oil from lavender can give relaxation (carminative), sedative, reduce anxiety level and increasing mood.